A Quiet Revolution in Chinese Universities: Experimental Colleges - Zha, Qiang; Yang, Qiubo (International Higher Education, 2014)
A quiet revolution might now be observed internally in Chinese universities, along with emergence of a group of experimental colleges/schools. These experimental units showcase a bottom-up approach to exercising democratic governance, whereby many grassroots initiatives could be identified and brought into the practices, and they are more likely to tap autonomous practices into existing operations, often in a genuine and innovative way.